Structure Design of Brake Controller Lateral Pressure Reset Device - DENG Lili; ZHU Lijun; LIN Ping; LI Yang (机车电传动)
This paper briefly introduced the basic structure and working principle of brake controller lateral pressure reset device. By calculating the routine distance and designing the reset spring, this design could realize the requirement of low-voltage interlocking switch electric signal output. This device could meet the requirement of locomotive braking, guarantee reliability of locomotive and train. The brake controller passed type test and circulate assess, and realized batch production.